Bioaccumulation of antibiotics and resistance genes in lettuce following cattle manure and digestate fertilization and their effects on soil and phyllosphere microbial communities. (15th December 2022) - Barra Caracciolo, Anna; Visca, Andrea; Rauseo, Jasmin; Spataro, Francesca; Garbini, Gian Luigi; Grenni, Paola; Mariani, Livia; Mazzurco Miritana, Valentina; Massini, Giulia; Patrolecco, Luisa
Abstract: The degradation and bioaccumulation of selected antibiotics such as the sulfonamide sulfamethoxazole (SMX) and the fluoroquinolones enrofloxacin (ENR) and ciprofloxacin (CIP) were investigated in soil microcosm experiments where  Lactuca sativa  was grown with manure or digestate (1%) and spiked with a mixture of the three antibiotics (7.5 mg/kg each). The soil, rhizosphere and leaf phyllosphere were sampled (at 0 and 46 days) from each microcosm to analyze the antibiotic concentrations, main resistance genes ( sul1, sul2,   qnrS, aac-(6')-Ib-cr and  qepA ), the  intI1 and  tnpA  mobile genetic elements and the microbial community structure.Overall results showed that SMX and CIP decreased (70-85% and 55-79%, respectively), and ENR was quite persistent during the 46-day experiment. In plant presence, CIP and ENR were partially up-taken from soil to plant. In fact the bioaccumulation factors were > 1, with higher values in manure than digestate amended soils. The most abundant gene in soil was  sul2  in digestate- and  aac-(6')-Ib-cr  in the manure-amended microcosms. In soil, neither sulfamethoxazole-resistance ( sul1  and  sul2 ), nor fluoroquinolone-resistance ( aac-(6')-Ib-cr,   qepA  and  qnrS ) gene abundances were correlated with any antibiotic concentration. On the contrary, in lettuce leaves, the  aac-(6')-Ib-cr  gene was the most abundant, in accordance with the fluoroquinolone bioaccumulation. Finally, digestate stimulated a higher soil microbial biodiversity, introducing and promoting more bacterial genera associated with antibiotic degradation and involved in soil fertility and decreased fluoroquinolone bioaccumulation. Graphical abstract: Image 1 Highlights: SMX and CIP decreased in manure and digestate amended soils, but ENR was quite persistent. CIP and ENR bioaccumulated in Lactuca sativa leaves. Plant presence decreased overall ARGs in rhizosphere. Digestate promoted higher bacterial diversity and lower fluoroquinolone bioaccumulation. Phyllosphere microbiota and ARB were influenced by amendments and antibiotics.